Hemorrhoids and pregnancy: modern ideas of treatment and prevention - S. V. Vasiliev; D. Y. Popov; A. I. Nedozimovannyi; O. S. Sokolova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
This article discusses issues related to the etiology, pathogenesis, clinical, prevention and treatment of hemorrhoids in pregnant and postpartum women. The evaluation of the need for and effectiveness of preventive treatment of exacerbations of hemorrhoids during pregnancy and the early postpartum period, pre-development of optimal efficiency and safety of treatments for hemorrhoids exacerbations during pregnancy. Applications submitted treatments and prevention can significantly reduce the risk of acute hemorrhoids and reduce terms of relief of symptoms in pregnant and postpartum women.